Elucidating the long-range charge carrier mobility in metal halide perovskite thin films - Lim, J; Hoerantner, M; Sakai, N; Ball, J; Mahesh, S; Noel, N; Lin, Y; Patel, J; McMeekin, D; Johnston, M; Wenger, B; Snaith, H (Royal Society of Chemistry, 2018)
Many optoelectronic properties have been reported for lead halide perovskite polycrystalline films. However, ambiguities in the evaluation of these properties remain, especially for long-range lateral charge transport, where ionic conduction can complicate interpretation of data. Here we demonstrate a new technique to measure the long-range charge carrier mobility in such materials. We combine quasi-steady-state photo-conductivity measurements (electrical probe) with photo-induced transmission and reflection measurements (optical probe) to simultaneously evaluate the conductivity and charge carrier density. With this knowledge we determine the lateral mobility to be ∼2 cm2 V−1 s−1 for CH3NH3PbI3 (MAPbI3) polycrystalline perovskite films prepared from the acetonitrile/methylamine solvent system. Furthermore, we present significant differences in long-range charge carrier mobilities, from 2.2 to 0.2 cm2 V−1 s−1, between films of contemporary perovskite compositions prepared via different fabrication processes, including solution and vapour phase deposition techniques. Arguably, our work provides the first accurate evaluation of the long-range lateral charge carrier mobility in lead halide perovskite films, with charge carrier density in the range typically achieved under photovoltaic operation.